Role of B-Scan Ultrasonography in Cataract Patients; A single Centered Cross-Sectional Study - Muhammad Saleem Akhter , Muhammad Rafi Abbas , Yasir Jamal , Zarlish Fazal , Usama Abdul Jabbar (Journal of Islamic International Medical College)
Objective: To assess lesions of the posterior segment in pre-operative cataract patients using B-Scan ultrasonography and to determine various risk factors contributing to posterior segment lesions. Study Design: A Descriptive Cross-Sectional Study Place and Duration of the Study: The study was conducted in the Department of Radiology, Sahiwal Teaching Hospital from 10 June 2022 to 10 December 2022. Materials and Methods: We enrolled 290 cases of cataracts including both genders and all ages, both with and without history of trauma. All cases underwent a B-Scan ultrasound to assess posterior segment pathologies. Patients having congenital lesions and with any history of surgery were excluded from the study. The data was analyzed using SPSS version 25.0. The frequencies and percentages of posterior segment pathologies observed on the B-Scan were calculated. The percentage of various co-morbidities contributing to posterior segmental lesions was also analyzed. Results: The mean age of the subjects was 36.0 + 23.2 years. 137 (47.2%) cases were females and 153 (52.7%) were males. Cataract was observed in 253 (87.2%) subjects without any trauma to eye. While studying various risk factors that increase the risk of lesions of the posterior segment, the most common were hypertension (17.5%) followed by diabetes mellitus (16.5%). Conclusion: We concluded that B-Scan is a valuable and easily available modality to detect posterior segment pathologies in cataract patients.